Nine new species groups, 15 new species, and one new subspecies of New Guinea diving beetles of the genus Exocelina Broun, 1886 (Coleoptera, Dytiscidae, Copelatinae) - Shaverdo, Helena (Zookeys, 2019)
Abstract. Nine new species groups of Exocelina Broun, 1886 from New Guinea are introduced with keys to their representatives. Four groups are monotypic and include three new species: the E. aipomek group, the E. koroba group: E. korobasp. nov., the E. mekilensis group: E. mekilensissp. nov., and the E. morobensis group: E. morobensissp. nov. The remaining five species groups include 18 species with 12 new species and one new subspecies: the E. bacchusi group: E. akamekusp. nov., E. oiwasp. nov., E. oksibilensissp. nov., and E. bacchusi herzogensisssp. nov.; the E. jaseminae group: E. asekisp. nov., E. kailakisp. nov., and E. pseudojaseminaesp. nov.; the E. larsoni group: E. warahulenensissp. nov.; the E. takime group: E. mianminensissp. nov.; and the E. warasera group: E. haiasp. nov., E. kobausp. nov., E. pulchellasp. nov., and E. waraserasp. nov. Diagnoses of five already described species of these groups are provided, as well as comparatives notes on all species. Exocelina santimontis (Balke, 1998) syn. nov. is a junior synonym of E. aipomek (Balke, 1998). Data on the distribution of the species are given, showing that most of the species of these groups occur in the Papua New Guinea.